Effect of reinforcement, compact pressure and hard ceramic coating on aluminium rock dust composite performance. (January 2016) - Soorya Prakash, K.; Sathiya Moorthy, R.; Gopal, P.M.; Kavimani, V.
Abstract: Aluminium 6061T6 is reinforced with naturally available rock dust particles to fabricate low cost aluminium rock dust composite through powder metallurgy technique. Reinforcement ratio was varied from 0% to 50% whereas size of the particles was kept constant as 20 μm. Mixed powders were compacted at three different pressures from 100 to 200 MPa. Al2 O3 ceramic coating was given over the novel composite material by Type III Sulphuric acid hard coating method. Developed composites were tested for microstructure, micro-hardness and wear resistance. SEM micrograph confirms uniform distribution of reinforcement in matrix and a fine ceramic hard coating is observed through optical microscopic images. Micro-hardness increases as reinforcement level increases up to 10%. Wear properties were analysed using pin on disc setup without lubricant and by maintaining three parameters viz load, sliding velocity and sliding distance being unchanged. It was found that composite with 10% rock dust gives better wear resistance than any other compositions. Also incrementing figure is notified for hardness and subsequently wear resisting property too when compacting pressure gets increased. Coated sample exhibits better performance than uncoated composite samples at all compositions and at different levels of compacting pressure. Highlights: A low cost hard rock dust is utilized as reinforcement. Composite is fabricated through powder metallurgy technique at different compacting pressures. Al2 O3 ceramic coating was given by Type III Sulphuric acid hard coating method. Density, micro-hardness and wear resistance of the composite were evaluated. Rock dust addition, compaction pressure and hard coating play significant role in material performance.